Does Kahoot Challenge Mode Motivate Students’ Better Than Google Form in Doing Online Homework? - Oza Anggia Fatmawati (STKIP PGRI Trenggalek, 2021)
Kahoot and Google Form, such as E-learning application commonly used in conducting online quizzes. This study is aimed to prove out whether the students’ implemented Kahoot Challenge Mode have better motivation than students implemented Google Form for their autonomous homework. The research design of this research is quantitative research method, and the approach is quasi-experimental. The sample is the second semester of English Language Education Department at STKIP PGRI Trenggalek. The researcher uses questionnaires to gain detail information about the students' perception of the implementation of Kahoot Challenge Mode and Google Form toward their motivation in their autonomous homework. The researcher uses the independent sample t-test formula to calculate the test result. After obtained the result, the researcher concluded that there is an effect on students’ motivational learning by using Google Form. The interpretation of this research was a positive influence on the motivation of English Language education students' studying program through Google Form but not with Kahoot Challenge Mode. So, the conclusion is that students who do independent assignments through Kahoot Challenge Mode do not have better motivation than students who do independent assignments using Google Form.